Synchronous motion of the Easter mantle plume and the East Pacific Rise - John M. O’Connor; Marcel Regelous; Karsten M. Haase; Christophe Hemond; Anthony A. P. Koppers; Daniel P. Miggins; Daniel E. Heaton (Nature Communications)
Abstract The Easter mantle plume has produced one of the longest hotspot tracks in the Pacific Ocean. While previous studies have focused on the eastern side extending across the Nazca Plate, we use 40Ar/39Ar isotopic and geochemical data to investigate the less explored western side around the Easter Microplate. We propose a dynamic model in which a deeper (600 km-depth), less buoyant mantle exerts a westward force on the East Pacific Rise (EPR), while a more buoyant plume region drives Easter hotspot volcanism and a localised acceleration in seafloor spreading. Our findings suggest that the Easter hotspot is the more focused surface expression of the most buoyant region of a vast, deep-seated mantle plume extending from the Pacific Large Low Shear Velocity Province (LLSVP). This challenges the traditional view of hotspots as isolated phenomena and suggests they are part of broader LLSVP-related mantle structures. Our results imply a more intricate, large-scale relationship between hotspots, mantle plumes, spreading ridges, and mantle dynamics.